The Production of Gelatin from Snapper Scales (Lutjanus camphecanus Sp.) through Enzymatic Pretreatment - Triastuti, Warlinda Eka; Suprapto; Agustiani, Elly; Qomariyah, Lailatul; Subyakto, Agung; Widasgantri, Treisnaning; K, Marchel Abednego Septa (IPTEK The Journal of Engineering, 2025)
Fish wastes such as fish bones and scales have a potential to be used as a gelatin source. It can be used as an alternative material to replace pork or bovine which ordinarily conflicted with religion issue. Gelatin from fish has different characteristics compared with mammalian source. It has several advantageous properties such as high amount of hydrophobic amino acids, less proline and hydroxy proline, lower gelling ability, and melting point. In this study, gelatin was produced from fish waste especially snapper scales using the bromelain enzyme at the pre-treatment stage to improve its characteristic. The snapper scales soaking in hot water at 80 degrees Celsius for about 30 minutes to remove the fat which attached the scales. A pre-treatment has been conducted using bromelain enzyme solution at various concentrations of 1 percent, 2 percent, 3 percent, 4 percent and 5 percent for 6 hours to remove non-collagenous proteins and loosen the bonds of the fish scales. The next step is demineralization using a 15 percent concentration of citric acid solution for 3 days. The ossein formed in the demineralization stage was then hydrolyzed at 50 degrees Celsius and 70 degrees Celsius for 9 hours with stirring at 300 rpm. The best gelatin yield was obtained from the pretreatment of bromelain enzyme solution with a concentration of 3 percent at a hydrolysis temperature of 70 degrees Celsius with a yield of 9.13 percent, pH value of 3.86, water content of 8 percent, ash content of 0.80 percent. FTIR spectra shows the presence of functional groups correspond to gelatin formation, such as carbon, hydrogen, hydroxyl group (O-H), carbonyl group (C=O), amine group (N-H) and alkene group (C=C). The heavy metal content test showed that the gelatin contained no heavy metal content of lead (Pb), mercury (Hg), cadmium (Cd) and arsenic (As).